Research Based Curriculum Development Model and Islamic Scientific Tradition In Senior High Education - Armayoga, Bagas; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Fitrah: Journal of Islamic Education, 2024)
Islamic education is faced with two dilemmas: the demands of modernism and the preservation of the Islamic scientific tradition. This dilemma requires Islamic educational institutions to accommodate both demands in the curriculum. SMA Negeri 1 Adiluwih seeks to develop a curriculum model that integrates modern research and Islamic tradition, which is the focus of this research, including the challenges faced. This research uses qualitative methods based on phenomenological studies with data collection techniques of observation, interviews, and documentation studies. The results reveal that efforts include improving teacher competence, integrating learning materials, and project-based learning. This research-based curriculum and Islamic tradition have positively contributed to the learning process by integrating Islamic values and encouraging students to think critically and reflectively. Development challenges include limited resources and external support, especially from parents. This research corroborates Fazlur Rahman's theory of reformulating Islamic education that integrates modern science with Islamic scientific traditions to answer the challenges of the times. Rahman emphasizes the importance of a research-based approach to building critical understanding, as applied in the curriculum model of SMA Negeri 1 Adiluwih.